Calculation of the shock temperature of moderately porous graphites. (July 2016) - Bourasseau, E.; Pineau, N.; Maillet, J.-B.; Dubois, V.
Abstract: Although shock temperature measurements are crucial for the construction of accurate equations of state, they still remain challenging: in the case of porous graphites, no experimental measurements of shock temperatures are available in the literature. In this paper we present a model, based on the equations of state of pure graphite and diamond, that reproduces the shock properties of moderately porous graphites, including shock temperatures. The key idea of this work is to perform a Bayesian calibration of a postulated function which links the composition of the system to the pressure along the Hugoniot, in order to obtain a PV curve compatible with the available experimental data. This method gives convincing results for several types of porous graphites with initial densities from 1.77 to 2.21 g cm −3, and allows to explain the disparities between their corresponding Hugoniot curves and the one of pure diamond at high pressure. Besides, we show that shock temperatures of porous graphite can be evaluated with satisfying uncertainty, opening the route to further improvements of the equations of state used in hydrodynamic simulations.